Investigation on the effects of multijet fusion printing parameters on porosity of mechanical properties of printed polymer parts - Kumar, Timothy Theodore (Nanyang Technological University, 2023)
The era of the fourth industrial revolution has acted as a catalyst for the development in additive manufacturing (AM) technology resulting in new, different and more creative ways of producing prototypes and changing the manufacturing industry. Hewlett-Packard (HP) have delved in the world of additive manufacturing by creating a Multijet Fusion (MJF) printer that fabricates nylon-based part.